(untitled) (INNOTEC, 2018)
Moringa stenopetala is a good source of nutrients intended for human and animal consumption. This fact inspired the study of its minerals and vitamin C contents. Metals were analyzed by flame atomic absorption spectrometry. Vitamin C was determined by liquid chromatography equipped with a diode array detector. The nutrients availability in infusions was evaluated by calculating transfer factors from the solid matrices. After analyzing several commercial brands, a greater variability in the content of elements such as iron, magnesium and sodium was observed. The high calcium content found in the samples was highlighted, but with a low transfer factor to the infusions. In the case of vitamin C, a great loss was detected during the preparation of the infusions due to thermal decomposition. Moringa stenopetala would be an interesting natural supplement beneficial to health, especially consumed on a fresh basis, rich in calcium, potassium, magnesium and vitamin C, in quantities like those present in foods recommended as a source of these nutrients.